2022
DOI: 10.14336/ad.2022.0826
|View full text |Cite
|
Sign up to set email alerts
|

Positive Feedback Regulation of Circular RNA Hsa_circ_0000566 and HIF-1α promotes Osteosarcoma Progression and Glycolysis Metabolism

Abstract: Hypoxia is an indispensable factor for cancer progression and is closely associated with the Warburg effect. Circular RNAs (CircRNA) have garnered considerable attention in molecular malignancy therapy as they are potentially important modulators. However, the roles of circRNAs and hypoxia in osteosarcoma (OS) progression have not yet been elucidated. This study reveals the hypoxia-sensitive circRNA, Hsa_circ_0000566, that plays a crucial role in OS progression and energy metabolism under hypoxic stress. Hsa_c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…In the process of OS metastasis ( Figure 6 ), Hsa-circ-0000566 is regulated by HIF-1α, and both directly binds to VHLE3 ubiquitin ligase protein to inhibit VHL-mediated ubiquitin degradation, thereby promoting their pivotal role in glycolysis of OS cells ( Shen et al, 2023 ). Mechanistically, protein arginine methyltransferase 9 (PrMT9) exerts control over HIF-1α through a distinct mechanism.…”
Section: Hif-1α and The Mechanism Of Os Metastasismentioning
confidence: 99%
“…In the process of OS metastasis ( Figure 6 ), Hsa-circ-0000566 is regulated by HIF-1α, and both directly binds to VHLE3 ubiquitin ligase protein to inhibit VHL-mediated ubiquitin degradation, thereby promoting their pivotal role in glycolysis of OS cells ( Shen et al, 2023 ). Mechanistically, protein arginine methyltransferase 9 (PrMT9) exerts control over HIF-1α through a distinct mechanism.…”
Section: Hif-1α and The Mechanism Of Os Metastasismentioning
confidence: 99%
“…Moreover, RIPK1 inhibitor reduced caspase-9-mediated apoptosis after rhabdomyolysis in rats [ 19 ]. In addition, hypoxia inducible factor 1-α (HIF-1α) is involved in regulation of biological functions such as inflammation and apoptosis which play a detrimental role in nervous system disorders [ 20 , 21 ]. HIF-1α exhibited an inflammation amplification effect [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…By screening the circRNAs that take part in cell growth, scholars found that the most of circRNAs not only play generic housekeeping roles but rather function in a regulatory and cell/tissue‐type‐specific manner 8 . Therefore, following the development of biotechnology, finding and analysing circRNAs has important clinical application value for drug action targets, gene therapy drugs or diagnostic biomarkers 9–11 …”
Section: Introductionmentioning
confidence: 99%
“… 8 Therefore, following the development of biotechnology, finding and analysing circRNAs has important clinical application value for drug action targets, gene therapy drugs or diagnostic biomarkers. 9 , 10 , 11 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation